Comment: Evidence for Basicness from Noise-like Interjections of Emotions. (January 2014) - Sauter, Disa A.
Goddard (2014) proposes a three-partite division of emotive interjections, which is helpful in delineating this heterogeneous set of phenomena. The distinction also explains inconsistencies between Goddard's and previous findings: While his study demonstrates variability across languages in word-like primary interjections, previous work investigating noise-like interjections has found evidence for universality. Such cross-culturally consistent, categorical perception of emotional signals can be explained as emerging from bottom–up information without the need for top–down learning via language or interjections.